Spontaneous Intracranial Hypotension: A Review of Neuroimaging and Current Concepts - Goddu Govindappa, Sharath Kumar; Adiga, Chaitra Parameshwara; Kumar, Savith; Goolahally, Lakshmikanth N.; Kumar, Sujit (Indian Journal of Radiology and Imaging, 2023)
Spontaneous intracranial hypotension (SICH) is the emerging cause of orthostatic headache as it has been better recognized in recent years. SICH happens due to spinal cerebrospinal fluid (CSF) leak; however, the manifestations are predominantly cranial and hence imaging in SICH includes brain and spine. There are few characteristic brain imaging features to be concerned about to diagnose SICH in patients with vague symptoms or low clinical suspicion. Spine screening is recommended in these patients to assess spinal CSF leaks. While neuroradiologists play a significant role from the time of diagnosis to treatment of SICH, there is a need for all the general radiologists to be aware of the condition. Computed tomography myelogram and digital subtraction myelogram are performed for diagnostic and therapeutic management of SICH. There is a known risk for SICH recurrence in patients with sagittal longitudinal epidural collection and hence, targeted blood patch should be used instead of blind patch. Most importantly, slow mobilization is recommended following the patch to avoid recurrence.
Keywords: spontaneous intracranial hypotension; CT myelography; orthostatic headache